An FFT approach for option pricing under a regime-switching stochastic interest rate model. Issue 11 (3rd June 2017) - Fan, Kun; Shen, Yang; Siu, Tak Kuen; Wang, Rongming
ABSTRACT: In this article, we investigate the pricing of European-style options under a Markovian regime-switching Hull–White interest rate model. The parameters of this model, including the mean-reversion level, the volatility of the stochastic interest rate, and the volatility of an asset's value, are modulated by an observable, continuous-time, finite-state Markov chain. A closed-form expression for the characteristic function of the logarithmic terminal asset price is derived. Then, using the fast Fourier transform, a price of a European-style option is computed. In a two-state Markov chain case, numerical examples and empirical studies are presented to illustrate the practical implementation of the model.